Pelvic inflammatory disease by actinomyces: report of 1 case and review of the literature - Camacho Herrera, Cesar Giovanni; Sanchez, Raul D. Lara; Garcia, Narmy Olivera; Bibiano, Karla E. Abundiz (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Actinomycosis is a chronic disease that is characterized by the formation of abscesses, fistulas and dense fibrous tissue at the site of involvement. Its distribution is worldwide. However, pelvic actinomycosis has increased in frequency and has been associated with abdominal surgery, intestinal perforation or trauma, due to the destruction of the muscular barrier. The clinical elements of suspicion are the latency of months and even years of symptoms and the history of being a carrier of an intrauterine device. Actinomyces israelli is a rare etiological agent of pelvic inflammatory disease, so it is difficult to reach the diagnosis. A case report is made of a 48-year-old patient with an intrauterine device older than 5 years, who entered the emergency department with abdominal pain syndrome and 7-day evolutionary fever accompanied by dyspareunia. She was hospitalized for antibiotic treatment, presenting an unsatisfactory evolution, with increased leukocytosis and persistent abdominal pain. An exploratory laparotomy with abdominal hysterectomy was performed. The histopathological diagnosis was pelvic inflammatory disease due to actinomyces. We must always suspect in the presence of a pelvic inflammatory disease in any of its clinical forms, the presence of actinomyces as one of the possible causative germs, especially in patients with intrauterine device for more than 5 years.